The Umboniinae (Mollusca: Gastropoda: Trochidae) of New Caledonia, with descriptions of two new genera and eight new species, plus an additional new species from the Bismarck Sea - David G. Herbert (European Journal of Taxonomy)
All species of Umboniinae known to occur in New Caledonia are discussed (19 species, 8 new, belonging to 10 genera, 2 new) and a key to genera is provided. An additional new species is described from the Bismarck Sea. Nine species are perhaps endemic to New Caledonia. The diversity of the fauna is comparable to that of Japan and Australia, both regions of much greater extent and spanning a much broader latitudinal range. Ethalia lampra (Watson, 1880), previously known only from the original HMS Challenger material from Fiji, has been rediscovered in New Caledonia. Re-examination of the type material of Monilea apicina Gould, 1861 has led to a re-interpretation of the application of this name. Type specimens of a number of additional umboniine species examined for comparison are illustrated. Two new genera are proposed: Kanakina gen. nov. and Tylorhaphe gen. nov. Nine new species are described: Ethalia anomphala sp. nov., Ethminolia hickmanae sp. nov., Sericominolia porcata sp. nov., S. safrocincta sp. nov., Talopena maestratii sp. nov., Tylorhaphe alisae gen. et sp. nov., T. fritillaria gen. et sp. nov., T. luteopicta gen. et sp. nov. and T. wallacei gen. et sp. nov. Revised status: Talopena Iredale, 1918 is recognised as a full genus rather than a subgenus or synonym of Monilea Swainson, 1840. Minolia agapeta Melvill & Standen, 1896 is considered a distinct species, no longer to be regarded as a junior synonym of Monilea apicina Gould, 1861. Trochus (Monilea) lifuanus Fischer, 1878 is considered a distinct species, no longer to be regarded as a junior synonym of Monilea vernicosa Gould, 1861. New combinations: Monilea incerta Iredale, 1912 is reassigned to Talopena Iredale, 1918; Monilea apicina Gould, 1861, Monilea menkei A. Adams, 1855, Monilea philippii A. Adams, 1855, Pseudominolia tramieri Poppe, Tagaro & Dekker, 2006, Trochus belcheri Philippi, 1850, Trochus calyculus W. Wood, 1828, and Trochus (Monilea) masoni G. Nevill & H. Nevill, 1874 are all referred to Talopena Iredale, 1918. Minolia glaphyrella Melvill & Standen, 1895 is transferred to Kanakina gen. nov. Type localities: Nouméa, New Caledonia is designated as the type locality for Trochus nucleus Philippi 1850; the type locality ‘Port Jackson’ originally given for Monilea apicina Gould, 1861 is considered erroneous and is emended to Lansdowne Bank. New records for New Caledonian marine ecoregion: Ethalia lampra (Watson, 1880), Talopena apicina (Gould, 1861) and ‘Talopena’ tramieri (Poppe, Tagaro & Dekker, 2006).